Predicting an investigation of flux distribution in three phase induction motor stators by using different stator slot sizes - Nor Shafiqin, Shariffuddin; Ismail, Daut, Prof. Dr.; Yanawati, Yahya; Pungut, Ibrahim; M., Abdullah; Nair, Gomesh (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.